KETERKAITAN ANTARA AGREGATE DEMAND DENGAN PERTUMBUHAN EKONOMI - Syaipan Djambak (Department of Development Economics, Universitas Sriwijaya, 2010)
Economic growth, is one measure of macroeconomic performance of an economy. Economic growth illustrates the ability of an economy in providing goods and services needs for the population of a country, so that high economic growth is the desire of each country because it can describe the country's prosperity. Since the economic recession experienced by Indonesia in 1987, Indonesia's economic growth is relatively small, where in 1987 the economic growth of minus 13.13 percent. Economic growth is so low, it is estimated by economists due to the low aggregate demand (AD) on the Indonesian economy, as well as the world economy, and therefore contributes to investment and economic growth in Indonesia. By using sequential equation model, the results of this study revealed that in aggregate demand (AD) has a significant positive effect on economic growth in Indonesia, although the coefficient is relatively low at only 4.99 percent. In addition, there are two variables aggregate demand, ie exports and imports variables did not significantly affect Indonesia's economic growth. Keywords: Aggregate Demand, Economic Growth